SELF-CONSCIOUSNESS, HEALTHY PERSONALITY AND SELFSYSTEM - Jiménez, José Antonio (Anales de Psicología / Annals of Psychology, 1999)
This paper is intended to be about the main subjectof psychology and especifically about the psychologyof personality in relation to the issue of self-attention. Thistheme constitutes basically the starting point of the differenttheories of objective self-awareness (e.g., Carver &Scheier, 1981; Duval & Wicklund, 1972...), and that it isone of the integral phenomenons of the " self " system (Fierro,1996).Within the pattern of these theories it has been studiedthe relationship of self-consciousness with variables suchas depression (Pyszczynski & Greenberg, 1985), anxiety(Dickstein et al. 1981), neuroticism (Wells & Matthews,1994), diverse somatic symptoms (Wells, 1991), etc., formingwith all them a defined pattern of relationships. In thisfield the studies about this subject are not very rich, especiallythose which are direct and explicit on the relationshiptaken place betwing self-attention and those variablesnearer to the healthy pole of the dimension healthypsychopathological.The present work seeks to throw some light on the relationshipthat keeps self-consciousness with some indicatorsof healthy personality informing of the found results(in two correlational studies) among self-focus, personalwell-being, social adaptation (direct indicators of healthypersonality), self-monitoring, implicit self-esteem and selfactualization.